UNLOCKING EMPLOYEE PERFORMANCE THROUGH DIGITAL LEADERSHIP AND MOTIVATION: THE MEDIATING ROLE OF INNOVATION (A STUDY OF THE PUNGGUL VILLAGE GOVERNMENT IN BADUNG REGENCY) - Sanjaya, I Gusti Ngurah Bagus; Novarini, Ni Nyoman Ari; Widyawati, Sapta Rini (EMAS, 2025)
The purpose of this study is to determine the effect of digital leadership and motivation on employee performance through innovation as a mediator. The population of this study was all 31 government employees of Punggul Village. The method used in determining the sample was nonprobability sampling. The sample in this study was all 31 government employees of Punggul Village. Data collection in this study was conducted using interviews and questionnaires. Data analysis in this study used the Partial Least Square (PLS) approach using SmartPLS software. The results of the study show that: 1) Digital leadership and motivation have a positive effect on innovation. 2) Digital leadership, motivation, and innovation have a positive effect on employee performance. These results mean that the better the implementation of digital leadership in the Punggul Village government, the higher the work motivation and innovation of employees in the Punggul Village government, and the higher the performance of employees in the Punggul Village government. 3) Innovation is able to partially mediate the influence of digital leadership and motivation on employee performance.